Pectoralis Major Flap: A Versatile Option for Head and Neck Reconstruction - A Case Report - Radot Oktora Tua Pasaribu; Affandi Wiramur; Joko Purnomo (HM Publisher, 2025)
Background: Skin flaps are an essential tool in reconstructive surgery, especially in the head and neck region where defects can result from tumor excision, trauma, or congenital anomalies. The pectoralis major flap is a well-established and versatile option for head and neck reconstruction due to its reliable vascularity, ease of harvest, and ability to cover a variety of defect sizes and locations. Case presentation: This report describes the case of a 22-year-old male with a history of parotid cancer who presented with a large, bleeding mass on the right side of his neck. Following tumor excision, the resulting defect was successfully reconstructed using a pectoralis major flap. Conclusion: The pectoralis major flap is a reliable and versatile reconstructive option for head and neck defects. It offers several advantages, including good vascularity, ease of harvest, and the ability to provide adequate tissue bulk for complex reconstructions.